Global dynamics, impasses of SUS and HEIC as a way out of the crisis - Gadelha, Carlos Augusto Grabois; Kamia, Felipe Duvaresch; Moreira, Juliana Duffles Donato; Montenegro, Karla Bernardo Mattoso; Safatle, Leandro Pinheiro; Nascimento, Marco Aurelio de Carvalho (Cadernos do Desenvolvimento, 2023)
This paper examines the context of production and innovation in health in Brazil and its response capacity to COVID-19 pandemic and discusses the possibility of connecting the assurance of universal access to health with a more equitable development pattern. It analyzes critical aspects of the geopolitics of innovation in health; how those dynamics interfere in the national sovereignty in health, as well as the main knowledge to be retained. Finally, we propose alternatives to avoid repeating the preventable difficulties that resulted from the pandemic. These alternatives arise from a shift in the perspective of public policy design and the incorporation of paradigms of the 4th technological revolution in public health, seeking to establish a structural connection between innovation and universal access in the context of the Unified Health System.